Recent advances in probabilistic species pool delineations - Dirk Nikolaus Karger (Frontiers of Biogeography)
A species pool is the set of species that could potentially colonize and establish within a community. It has been a commonly used concept in biogeography since the early days of MacArthur and Wilson’s work on Island Biogeography. Despite their simple and appealing definition, an operational application of species pools is bundled with a multitude of problems, which have often resulted in arbitrary decisions and workarounds when defining species pools. Two recently published papers address the operational problems of species pool delineations, and show ways of delineating them in a probabilistic fashion. In both papers, species pools were delineated using a process-based, mechanistical approach, which opens the door for a multitude of new applications in biogeography. Such applications include detecting the hidden signature of biotic interactions, disentangling the geographical structure of community assembly processes, and incorporating a temporal extent into species pools. Although similar in their conclusions, both ‘probabilistic approaches’ differ in their implementation and definitions. Here I give a brief overview of the differences and similarities of both approaches, and identify the challenges and advantages in their application.